2015
DOI: 10.1080/2162402x.2015.1073882
|View full text |Cite
|
Sign up to set email alerts
|

TIE-2-expressing monocytes are lymphangiogenic and associate specifically with lymphatics of human breast cancer

Abstract: In experimental mouse models of cancer, increasingly compelling evidence point toward a contribution of tumor associated macrophages (TAM) to tumor lymphangiogenesis. Corresponding experimental observations in human cancer remain scarce although lymphatic metastasis is widely recognized as a predominant route for tumor spread. We previously showed that, in malignant tumors of untreated breast cancer (BC) patients, TIE-2-expressing monocytes (TEM) are highly proangiogenic immunosuppressive cells and that TIE-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 56 publications
1
63
0
1
Order By: Relevance
“…Lehmann et al. [5] have proposed one of the most frequently used subclassifications, which includes 4 subtypes: 2 basal-like (BL1 and BL2), a mesenchymal, and a luminal androgen receptor subtype.Approximately 70% of TNBCs contain 20% or more tumor-infiltrating lymphocytes (TILs) in the tumor stroma [6]. The generally higher level of TILs and the higher expression of immune checkpoint molecules in TNBC compared with ER-positive (ER+) BCs also makes TNBC an attractive target for immunotherapy.…”
mentioning
confidence: 99%
“…Lehmann et al. [5] have proposed one of the most frequently used subclassifications, which includes 4 subtypes: 2 basal-like (BL1 and BL2), a mesenchymal, and a luminal androgen receptor subtype.Approximately 70% of TNBCs contain 20% or more tumor-infiltrating lymphocytes (TILs) in the tumor stroma [6]. The generally higher level of TILs and the higher expression of immune checkpoint molecules in TNBC compared with ER-positive (ER+) BCs also makes TNBC an attractive target for immunotherapy.…”
mentioning
confidence: 99%
“…detected TEM in human tumors, including those of the kidney, colon, pancreas and lung as well as soft tissue carcinomas, while they were excluded from surrounding healthy tissues 15 . We made similar observation in human breast cancer (BC) and reported that TEM are also highly pro-angiogenic 16 and pro-lymphangiogenic cells 17 . Further, TEM display an immune suppressive activity evidenced by their ability to secrete IL-10 and VEGF in large amounts and to dampen in vitro tumor-specific T-cell proliferation mediated by tumor dendritic cells (DC) 18 .…”
Section: Introductionmentioning
confidence: 54%
“…and further work is required to establish whether mouse and human TMEM have parallel functions and share similar mechanisms of tumor cell intravasation. Along these lines, we show that a fraction of TEM were found inserted into tumor lymphatics, but not with lymphatics of adjacent non-neoplastic tissue, where TEM show drastically reduced expression of TIE-2 and LEC markers 17 . Interestingly, we observed that all BC patients with metastasis to the lymph node (LN) show TEM inserted into their tumor lymphatics, whereas this was only the case for 57% of the patients without LN metastasis.…”
Section: Other Solid Tumor Typesmentioning
confidence: 63%
See 2 more Smart Citations